2003
DOI: 10.1016/s0002-9440(10)63642-5
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Postproteomic Characterization of Keratan Sulfate-Glycanated Isoforms of Thyroglobulin and Transferrin Uniquely Elaborated by Papillary Thyroid Carcinomas

Abstract: Previous studies have suggested that surface components of papillary thyroid carcinoma (PTC) cells may be aberrantly glycanated, but the precise nature of these molecules has not been unveiled nor documented to be of clinical relevance. A monoclonal antibody was raised against a unique keratan sulfate (KS) determinant and used to differentially screen benign and malignant thyroid tissue for the expression of components carrying these moieties. In a total of 349 cases of benign and malignant thyroid lesions, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Many reports have shown that proteins containing sulfated glycans (i.e., sulfated glycoproteins) are associated with various diseases, such as cancer [1,2], cystic fibrosis [3,4], and osteoarthritis [5][6][7]. Most of these reports have indirectly demonstrated the presence of sulfated glycoproteins by experiments using sulfotransferase genes, specific antibodies for a particular sulfated glycans, and/or radioisotope [ 35 SO 4 ] labeling [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have shown that proteins containing sulfated glycans (i.e., sulfated glycoproteins) are associated with various diseases, such as cancer [1,2], cystic fibrosis [3,4], and osteoarthritis [5][6][7]. Most of these reports have indirectly demonstrated the presence of sulfated glycoproteins by experiments using sulfotransferase genes, specific antibodies for a particular sulfated glycans, and/or radioisotope [ 35 SO 4 ] labeling [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Keratan-sulphate (KS) is a glycoprotein complex having an unusual relative ratio of highly sulphated disaccharides and carrying a novel non-characterized oligosaccharide moiety at the non-reducing terminus, which is recognized by the monoclonal antibody 373E1 (Magro et al 2003). This aberrant glycoprotein complex has been found almost exclusively in thyroid papillary carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…This aberrant glycoprotein complex has been found almost exclusively in thyroid papillary carcinomas. Moreover, it has been reported that papillary carcinoma-specific KS-bearing macromolecules are unique glycoforms of thyroglobulin and transferrin (Magro et al 2003). The peculiar KS epitope has been proposed as a novel marker for the differential diagnosis of benign and malignant thyroid tumours (Magro et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors' speculation that thyroglobulin (Tg) in thyroid cancer patients might differ from ordinary Tg, potentially rendering it more immunogenic, is supported by several previous publications since the 1980s through to the more recent past (6,7). Whether such increased Tg immunogenicity would translate into different epitope recognition patterns remains Department of Laboratory Medicine and Pathology, Mayo Clinic, Rochester, Minnesota.…”
mentioning
confidence: 99%